REAL-TIME CORRELATION ANALYSIS MONITORING SLOPE MOVEMENT USING SLOPE STABILITY RADAR (SSR605-XT) WITH ROCK MASS RATING AND ALTERATION TYPE DATA - Wijaya, R. Andy Erwin; Putra, Bayurohman Pangacella; Mamonto, Tesya Puspita (Institut Teknologi Sepuluh Nopember, 2025)
The North Main Ridge Pit location is an open gold mining area with several benches and steep slopes, which have the potential to cause landslides. Therefore, monitoring slope movements is crucial to reducing landslide risks and ensuring safe mining activities. This monitoring utilizes real-time methods directly within the mine pit using the Slope Stability Radar (SSR605-XT) tool. Data obtained from radar monitoring is analyzed using the IQ Monitor software to acquire information on slope deformation and movement speed. Mapping within the mine pit is conducted by measuring a distance of 5 meters for each segment, with a total length of 575 meters divided into 115 segments. The condition of the monitoring site at the mining level, characterized by significant slope movements, is heavily influenced by data estimates of rock mass assessment and alteration types. The weaker the rock mass class (3 and 4) and the argillic alteration type, the potential for slope movement to occur. On the other hand, the stronger the rock mass class (1 and 2) and the silicic and advanced argillic alteration, the less slope movement.